Digital competencies of Peruvian teachers in basic education - Hurtado-Mazeyra, Alejandra; Núñez-Pacheco, Rosa; Barreda-Parra, Aymé; Guillén-Chávez, Evelyn-Paola; Turpo-Gebera, Osbaldo (Frontiers in Education, 2022)
Digital teaching competence is directly related to the knowledge, use of Information and Communication Technologies (ICTs). Its use in educational contexts and processes seeks to integrate technology and pedagogy. The objectives of this study are to evaluate the level of Digital Teaching Competencies (DTCs) possessed by basic education (BE) teachers in different Peruvian schools and their comparison by competency area, considering sociodemographic factors. The research responds to a quantitative methodological approach. A non-experimental design of a comparative descriptive type was used, and a non-probabilistic purposeful sampling was applied. A total of 3,142 BE teachers participated in the study, including the educational levels of preschool (0–5 years), primary school (6–11 years), and Secondary school (12–16 years), belonging to public institutions located in rural and urban areas of the province of Arequipa (Peru). The instrument developed in the European Framework of Digital Competence, DigCompEdu Check-In, was applied. This instrument aimed to measure teachers’ level of competence in the digital domain. The main results show that a more significant number of teachers present an Integrator competence level (B1), followed by the Expert level (B2), and the Explorer level (A2). Furthermore, low percentages are observed in the most advanced leadership levels, Leader (C1) and Pioneer (C2), in the use of ICTs. The results obtained suggest implementing new strategies to improve DTCs. Based on critical conceptions, technology constitutes an essential tool for education in the twenty first century.